The Use of the ERP Systems: What Impact on Management Control Performance? - Hala, Hala; Achraf Nafzaoui, Mohamed (International Journal of Engineering and Technology, 2019)
Due to the huge advances in the digital world, companies have witnessed a rapid growth in their information systems. Management control, which constitutes a key element of permanent pilotage to many executives, who rely on accounting records, was thoroughly influenced by the adoption of Enterprise Resource Planning (ERP).Much research was done on the impact of information systems on management control and have illustrated that these systems and mainly ERP systems contribute to the evolution of management control.Our main aim in this work has many folds. First, we would like to set forth the main literature reviews on ERP systems and management control in order to clarify the conceptual changes of these terminologies, then deal with the relation that exist between them, by collecting theoretical assertions as well as empirical evidence.This paper in fact aims to shed light on the real impact of ERP systems on management control performance.Â Â